Coping with Stress in Athletes: Psychological Strategies and Psychometric Tools for Stress and Anxiety Assessment - Franciszek Kaczmarek; Monika Matecka; Joanna Bartkowiak-Wieczorek; Michał Kmiecik; Katarzyna Kaczmarek; Paulina Gajniak; Mateusz Fiutak; Joanna Stężycka; Kamil Krzysztof Krupa; Sonia Marchwiak; Michał Nowak; Michalina Cuper; et al. (Journal of Clinical Medicine, 2026)
Background and objectives: It is now increasingly acknowledged that psychological resilience and effective stress management are important factors in determining performance in professional sport. The present review examines various psychological interventions used in sport psychology, with particular emphasis on methods for improving performance under competitive pressure. It also assesses the psychometric scales and paradigm-based tools available for measuring stress, stress reactivity, and pre-competition anxiety in athletes. Methods: A narrative review was carried out using the OVID, EBSCO, PubMed, SCOPUS, Web of Science, and Google Scholar databases, with a preference for randomised controlled trials, observational studies, systematic reviews, meta-analyses, and consensus guidelines. Results: The results form the foundation for creating more thorough athlete support programmes. Psychological interventions are necessary to improve or maintain sporting performance, manage stress and anxiety, promote healthy sleep habits, and reduce the risk of injury. Conclusions: Athletic performance is influenced by technical, tactical, physical, and psychological factors. Psychological interventions, including self-talk, imagery, goal setting, mindfulness, and relaxation techniques, help manage stress while maintaining focus and motivation. It is recommended that athlete sleep education and psychosocially informed injury prevention be incorporated into these strategies.